THE RELATIONSHIP OF SECOND LANGUAGE ACQUISITION (SLA) IN ELT - Tiara Widyaiswara; Dian Luthfiyaty; Moh. Nurman (Faculty of Letters Universitas Balikpapan, 2024)
Second language acquisition (SLA) has been an important topic of research within the field of English Language Teaching (ELT), with numerous teaching methods and approaches being examined to better language learning. One of the most prominent figure is Stephen Krasen. Krasen develop monitor theory by five hypotheses that relate to a framework for teaching a providing second second language namely: the acquisition and learning hypothesis, the natural sequence hypothesis, the simple present tense structure will be acquired and mastered first by learners than the simple past tense structure, the Monitor Hypothesis, the input hypothesis, the affective filter hypothesis. Through the monitor exists in learning is a tool to